Engineering a multivalent antibody nanoparticle to overcome SARS-CoV-2 Omicron immune evasion - Sun, Hui; Jiang, Yanan; Lan, Miaolin; Zhou, Ming; Yi, Gangshun; Shen, Juan; Deng, Tingting; Liu, Liqin; Huang, Yang; Li, Yu; Su, Jinfu; Lin, Yanling; et al. (PLOS Pathogens, 2025)
The rapid evolution of SARS-CoV-2 and the subsequent emergence of Omicron subvariants pose significant challenges to the efficacy of existing vaccines and therapeutics, including those previously reported most broad neutralizing antibodies (bnAbs). Here, we investigated the molecular basis of the altered neutralization profile of a bnAb, 1C4, against recent variants. 1C4 is effective against early variants from Alpha to Omicron BQ.1, but is circumvented by BQ.1.1, XBB and thereafter variants, primarily due to an additional R346T mutation that diminishes its binding affinity. Cryo-electron microscopy analysis revealed that despite the loss of neutralizing potency, 1C4 retained residual binding to the spike protein of immune-evasive variants such as XBB, which harbor altered receptor-binding domain (RBD). Furthermore, 1C4 exhibited a diminished capacity to inhibit ACE2 engagement with Omicron variants, amplifying the intricacies of viral immune evasion tactics. To address this, we employed the mi3-SpyCatcher-based nanoparticle to polymerize 1C4 (mi3-1C4), which reestablished the neutralization potency against recent variants by enhancing avidity via multivalent binding. Such multivalent binding can promote efficient spike aggregation as well as viral cross-linking, thereby providing enhanced protection against both the infection of Beta and XBB variants in a hamster model. Together, our findings delineate the molecular landscape of immune evasion by neutralizing antibodies and provide strategic insight for the adaptation of antibody engineering to keep pace with viral evolution.